BIBLIOMETRIC ANALYSIS ON MONETARY POLICY TRANSMISSION THROUGH THE BANK LENDING CHANNEL - Abdul Hayy Haziq, Mohamad; Rossazana, Ab-Rahim; MOHD SUFFIAN, MOHAMED ESA; WEI, GAN JIA (Seybold Publication, 2024)
In the dynamic landscape of monetary policy and the bank lending channel, a comprehensive overview spanning over two decades unveils compelling insights into the trajectory of research and its future directions. This study aims conduct an overview of monetary policy and bank lending channel literature spanning 2000 to 2023. This study observes a sample of 301 documents from the Scopus database and using the software tools like VOSviewer, OpenRefine, and Harzing's Publish or Perish to analyses the data for extracted high impactful results. Three major findings emerged based on this review. First, United States stands out as the most productive and influential country, with 93 total publication and 5025 total citations in a country. Second, the Journal of International Money and Finance stands out as a premier publication venue in the realm of monetary policy and bank lending channel research. Finally, the most significant influence author is Gambacorta, as his articles has exerted a profound influence in the realm of monetary policy and the bank lending channel. His significant number 9 total publications and gain 1169 number citation; thus, reflect the depth, relevance, and impact of his research. This study also explores a colours cluster of all keywords and terms (based of title and abstract) of the co-occurrence map for identified the themes among the clusters.